Preliminary Investigation dan Requirement Analysis Phase untuk Membangun Aplikasi Borang Akreditasi - Dewi Kania Widyawati; Zuriati Zuriati (Jurnal Ilmiah ESAI, 2016)
The FAST (Framework for the Application of System Thinking) method can be implemented in education in the accreditation application development process. The first stage of the FAST method of Preliminary Investigation and Requirement Analysis Phase is very influential in the next stage of Decision Analysis Phase as a spear to analyze the needs what is needed to build the forms of accreditation application. In the Preliminary Investigation and Requirement Analysis Phase stage, we can find out the information / data needed for each accreditation form standard, and can understand the ongoing system implemented in the form of mapping chart image. Keywords: Mapping Chart, Preliminary Investigation, Requirement Analysis Phase